CURRENT PROBLEMS OF MODERN ONCOGYNECOLOGY: UTERINE SARCOMAS - A. G. Solopova; A. D. Makatsariya; A. E. Solopova; I. A. Rozanov; E. K. Titova (Акушерство, гинекология и репродукция, 2017)
The aim of this study was to review and analyze the medical reports on the current aspects of etiology, pathogenesis, diagnosis and treatment of uterine sarcomas. Here, we attempt to summarize the available information concerning the patient management and the many issues related to the diagnosis and treatment of this disease. In this study, the updated classification of uterine sarcomas is presented together with the current concepts on staging of the disease. Although «epidemiologically» rare, this group of diseases represents a serious oncological problem because of its severity and high mortality rate, and the lack of complete understanding of its pathogenesis.